Association between glycemic control and chronic kidney disease development in older patients with type 2 diabetes: A retrospective cohort study - Mar Riera-Pagespetit; Gorka Gómez-Terrazas; Doris Xiomara Monroy-Parada; Cristian Tebé; Carlos Pérez-López; Silvia Miró Cañís; María José Castro-Castro; Anna Cortés-Bosch de Basea; Alejandro Rodríguez-Molinero (PLoS ONE, 2026)
Background In older patients with type 2 diabetes (T2D), physicians often de-emphasize strict glycemic control to avoid severe hypoglycemia. However, the incidence of renal impairment in diabetic octogenarians is underexplored, and the impact of glycemic control on kidney function in this age group remains unclear. This study assessed its effect on CKD development. Methods Retrospective, multicenter cohort study including patients (>80 years) with T2D between 2012 and 2016, at least one annual glycated hemoglobin (HbA1c) measurement, an estimated glomerular filtration rate (GFR) ≥60 mL/min/1.73m 2 , and ≥one annual GFR estimation during follow-up. Patients were classified according to glycemic control (poor and good); good control was set at HbA1c < 7.5%. Five-year follow-up data were collected from medical records. Results The study included 1062 patients, 435 (40.96%) in the poor glycemic control group and 627 (59.04%) in the good control group. CKD incidence was significantly higher among individuals with poor control (61.61%) compared to those with good control (52.47%) (p = 0.003). Logistic regression analyses showed that poor control is independently associated with higher odds of CKD onset (OR: 0.87 good vs. poor control, p = 0.010) and accelerates its progression (time-to-CKD HR: 0.78 good vs. poor control, p = 0.004). Conclusions Poor glycemic control is independently associated with CKD development and a shorter time to CKD onset, supporting its potential relevance for kidney-related outcomes in older patients with T2D. These findings highlight the need to consider glycemic control within a broader, individualized clinical approach in this population.